PARASITISMO DE Eutrichopodopsis nitens Blanchard (DIPTERA; TACHINIDAE EM ADULTOS DE Nezara viridula (L.) (HEMIPTERA â€“ HETEROPTERA, PENTATOMIDAE) EM CURITIBA, PARANÃ - Santos, Benedito Baptista dos; Silva, LuÃs Antonio Torres da (REVISTA DE AGRICULTURA, 2015)
PARASITISMO DE Eutrichopodopsis nitens Blanchard (DIPTERA; TACHINIDAE EM ADULTOS DE Nezara viridula (L.) (HEMIPTERA â€“ HETEROPTERA, PENTATOMIDAE) EM CURITIBA, PARANÃ